2016
DOI: 10.1556/1846.2016.00003
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Optimization of Diazotization and Phase Transfer Catalyzed Azo-Coupling Reactions in Microreactors

Abstract: Herein, we illustrate how microreactor technology can be used as a tool for reaction screening and optimization, in addition to improving the reaction chemistry. We report the in-situ generation of azo compounds by reactive quenching of diazonium intermediates in microreactors. This involves an electrophilic aromatic substitution reaction, namely, an azo-coupling reaction performed in continuous-flow systems in the presence of a phase transfer catalyst with great emphasis on compounds that do not easily couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The continuous-flow synthesis of azo dyes in a microreactor system was also studied. The synthesis of the azo dye was the same as that of azo pigments, and as reported in the literature, excellent results, such as a high product yield and selectivity and a short reaction time were obtained by using microreactor technology. However, to date, there are few reports about the continuous-flow synthesis of C.I. PR 146 in a microreactor system.…”
Section: Introductionmentioning
confidence: 82%
“…The continuous-flow synthesis of azo dyes in a microreactor system was also studied. The synthesis of the azo dye was the same as that of azo pigments, and as reported in the literature, excellent results, such as a high product yield and selectivity and a short reaction time were obtained by using microreactor technology. However, to date, there are few reports about the continuous-flow synthesis of C.I. PR 146 in a microreactor system.…”
Section: Introductionmentioning
confidence: 82%
“…In 2016, Akwi and Watts reported the use of continuous flow, microreactors, and phase transfer catalysis (PTC) in the generation azo compounds, Fig. 10 [ 33 ]. Here they utilized a phase transfer catalyst in a liquid– liquid Taylor droplet flow reaction system for the in-situ reactive quench of diazonium salts.…”
Section: -2016mentioning
confidence: 99%
“…To increase the conversion of the coupling reaction, Watts et al predicted and analysed the effect of coupling conditions on reaction conversion and the effect of various parameters on the synthesis of Sudan II azo dye (5) in glass Little Things Factory-MS (LTF-MS) microreactors using the STATISCA 12 -Statsoft program (Scheme 4). 92,93 Of the three parameters of the coupling reaction, temperature, pH, and the flow rate of the coupling reagent, it was found that the pH has the most significant effect on the coupling reaction and that the temperature and flow rate have little effect. This finding is similar to most reports on the effect of temperature and flow rate in the single-step synthesis of azo compounds in continuous flow systems; the effect of temperature is negligible, and the effect of mass transfer is the most significant.…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%
“…93 Furthermore, the same group successfully explored surfactants, such as sodium dioctyl sulfosuccinate, as phase transfer catalysts to promote azo coupling reactions in continuous flow systems. 92,94 The addition of a phase transfer catalyst is conducive to the coupling of waterinsoluble coupling agents (e.g., phenol and aniline), which can promote the reduction of the surface tension between the liquid and the liquid phase and stabilize the formation of the liquid-liquid interface. The closer the added amount is to the critical micelle concentration, the more stable the effect of the phase transfer catalyst (Fig.…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%